ANALISIS KEMAMPUAN GURU DALAM PENGEMBANGAN MODUL AJAR DAN MEDIA PEMBELAJARAN DALAM PROSES BELAJAR MENGAJAR DI KELAS V SDN 80/I MUARA BULIAN - Bella Silvesteria Damanik; Annisa Amalia; Adelia Nur Tahira; Natasya Agustin; Cindi Sandra; Khoirunnisa; Muhammad Sofwan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The study aims to describe the ability of teachers in developing teaching modules and learning media in teaching and learning activities in class V of SDN 80/I Muara Bulian. This study is a qualitative descriptive study with three data collection techniques, namely observation, interviews, and documentation with the research subjects being the Principal, teachers and students. The data was analyzed using data triangulation by collecting, sorting data, displaying data and drawing conclusions. The results of the study indicate that in the development of teaching modules, SDN 80/I Muara Bulian has used it and adjusted it since 2022. The development of teachers' abilities in compiling teaching modules is carried out by training alternately to all class teachers. Like wise with learning media, teachers have received training in the development of learning media which is expected to be able to sort and use teaching modules and learning media properly and be useful for improving student learning. Some obstacles in this development are 1) teachers do not understand technology, 2) Teachers do not understand the components and structure of teaching modules, , 3) adjustments to the use of the independent curriculum which is quite long and 4) teachers are less competent in the learning process, especially in selecting the right teaching media. The solution to overcome the obstacles is through learning training, providing adequate facilities, especially infrastructure and facilities, and helping each other between teachers in preparing learning media.